Breast Pathology in the Department of Gynecologic Oncology Central Hospital No. 2 Peru's Social Security - Núñez Vidalón, Ricardo (2015)
Experience occurs during the first three years, in terms of breast pathology at the Department of Gynecologic Oncology Central Hospital No. 2 Social Security of Peru 854 of a total of 2,785 cases had some type of breast disease, highlighting in decreasing order frequency; painful dysplasia, fibroadenoma, fibrocystic dysplasia, etc., breast cancer ranked sixth. The most common symptoms were latumoración consultation and breast pain. The period of life most affected is between 30 and 50 years old.